Appropriation, Human Capital, and Mandatory Schooling - Amihai Glazer; Mark Gradstein (Center for Economic Studies and ifo Institute (CESifo), 2001)
Reduced inequality in human capital may reduce appropriationfrom the rich. They may therefore favor policies such as incometransfers and mandatory schooling which equalize human capital.Comparing several such policies, we find that mandatory schooling leads to higher incomes for both the rich and the poor, and increases the welfare of all. Moreover, it is the optimal policyfor the rich, even when they fully pay for the education.
Keywords: 330